The Role of Æschere's Head. (24th December 2016) - Appleton, Helen
Abstract: This article draws on evidence from archaeological investigation and land charters to argue for the influence of Anglo-Saxon execution practice on the representation of Æschere's head in Beowulf . The poet's depiction of the discovery of the severed head of Hroðgar's retainer in a space defined as a borderland, where it has been left by his killer, Grendel's mother, can be seen to reflect the Anglo-Saxons' own judicial decapitation and display practices, which saw the heads of transgressors displayed on estate boundaries. Critics have identified similar echoes of decapitation on a border elsewhere in the corpus. The article argues that the severed head of Æschere is staged in this way to disturb the reader both through the violence done to the human body and through the sense of the unheimlich created by the hostile 'other' figure of Grendel's mother recognisably echoing the corporal punishment practices of Anglo-Saxon society. Grendel's mother is a transgressive figure who treats a key member of the Danes' society, an individual with whom the poem's Anglo-Saxon audience would identify, as a transgressor, highlighting the lack of human control over her landscape.